2020
DOI: 10.3389/fneur.2020.00417
|View full text |Cite
|
Sign up to set email alerts
|

Erenumab in Chronic Migraine Patients Who Previously Failed Five First-Line Oral Prophylactics and OnabotulinumtoxinA: A Dual-Center Retrospective Observational Study

Abstract: Background: German authorities reimburse migraine prevention with erenumab only in patients who previously did not have therapeutic success with at least five oral prophylactics or have contraindications to such. In this real-world analysis, we assessed treatment response to erenumab in patients with chronic migraine (CM) who failed five oral prophylactics and, in addition, onabotulinumtoxinA (BoNTA).Methods: We analyzed retrospective data of 139 CM patients with at least one injection of erenumab from two Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
4
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 32 publications
8
56
4
15
Order By: Relevance
“…All converters withhold medication overuse. The high rate of conversion to EM in our population of di cult-to-treat patients with a long history of CM and multiple prior preventive treatment failures, including botulinum toxin in ≥ 40% of cases, supports the e cacy of erenumab for the preventive treatment of patients with CM, as shown in randomized controlled trials [13][14][15][16][17][18] and real-life studies [7][8][9][10]. We also found that at Months 4-6 16.5% of patients achieved a status of LFEM, while 28.6% achieved a status of MFEM, which indicates a high treatment bene t and a substantial improvement in the patients' quality of life.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…All converters withhold medication overuse. The high rate of conversion to EM in our population of di cult-to-treat patients with a long history of CM and multiple prior preventive treatment failures, including botulinum toxin in ≥ 40% of cases, supports the e cacy of erenumab for the preventive treatment of patients with CM, as shown in randomized controlled trials [13][14][15][16][17][18] and real-life studies [7][8][9][10]. We also found that at Months 4-6 16.5% of patients achieved a status of LFEM, while 28.6% achieved a status of MFEM, which indicates a high treatment bene t and a substantial improvement in the patients' quality of life.…”
Section: Discussionmentioning
confidence: 57%
“…Monoclonal antibodies directed against the calcitonin gene-related peptide (CGRP) or its receptor (CGRPr) are migraine-speci c treatments whose e cacy and safety were proven in both EM and CM [2][3][4][5]. However, the available real-life studies show that most patients treated in common clinical practice have CM [6][7][8][9][10]. In the present real-life, multicenter study, we assessed the rate and possible predictors of conversion from CM to EM in patients treated with erenumab.…”
Section: Introductionmentioning
confidence: 99%
“…A previous real-life study found a trend toward better response to erenumab in triptan responders compared with non-responders [11], being however underpowered to draw de nite conclusions. The remaining available real-life studies on the safety and e cacy of erenumab [12][13][14][15][16][17] did not assess triptan response. Our nding is in line with a previous report which found an association between response to triptans and response to onabotulinumtoxin A [18]; however, the association found by this early study was not con rmed in a further study [19].…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies directed against the calcitonin gene-related peptide (CGRP) or its receptor (CGRPr) are migraine-specific treatments whose efficacy and safety were proven in both EM and CM [5][6][7][8]. However, the available real-life studies show that most patients treated in common clinical practice have CM [9][10][11][12][13]. In the present real-life, multicenter study, we assessed the rate and possible predictors of conversion from CM to EM in patients treated with erenumab.…”
Section: Introductionmentioning
confidence: 99%